Editorial Commentary : Hip Microinstability: From Diagnostic Chaos to Clinical Precision - Vikas Khanduja (Arthroscopy, 2026)
Abstract Hip microinstability is now widely accepted as a distinct clinical entity, yet consensus on how to diagnose it remains elusive. A current systematic review found 23 studies proposing 32 distinct diagnostic criteria across clinical history, physical examination, imaging, and intraoperative findings, evidence of a field still searching for a unified standard. Intraoperative ease of distraction, the most cited criterion, lacks reproducibility across surgeons and centers, whereas the hyperextension‐external rotation test offers the most robust physical‐examination data. Imaging markers like the femoroepiphyseal acetabular roof index, cliff sign, and capsular thinning on magnetic resonance imaging represent the strongest objective gains, though overlap with borderline dysplasia remains unresolved. Existing Delphi consensus frameworks provide structure but require prospective, multicenter validation. This commentary argues that the field must move beyond a binary diagnosis toward phenotypic characterization, stratifying patients by mechanical instability pattern rather than treating all cases identically, and calls for prospective, outcome‐linked research to convert expert pattern recognition into evidence‐based diagnostic certainty.